PARTISIPASI MASYARAKAT DALAM MEMBERDAYAKAN SISKAMLING - Deta Marsela; Bayu Pradikto (UNIB Press, Universitas Bengkulu, 2021)
The purpose of this research is to describe the community participation in empowering the mobile security system. This research is a qualitative descriptive research. This study uses interview data collection techniques, observation and documentation. Checking the validity of the data used triangulation of sources, triangulation of time and triangulation of techniques. The results obtained from the research are the participation of citizens in participating in the security system at Neighborhood Association 19, Cempaka Permai Village, including the participation of thoughts, energy, assets, skills and skills as well as social participation. On the other hand, there is also internal citizen participation and external participation of residents in participating in the participation system of the Neighborhood Association residents around them supporting and attending even though they do not participate in patrols, from agencies from Babinsa, Bhabinkamtibmas, Head of Rukun Warga, Head of Subdistrict, then from the Mayor's Government give an award, one of them is the Bengkulu City Political and National Unity Body.